Preliminary observations on artificial fecundation, hatching and developmental stages of embryo and larvae of the Indian shad Tenualosa ilisha (Hamilton, 1822) - Chattopadhyay, D. N.; Chakraborty, A.; Ray, P. K.; Jayasankar, P. (Indian Journal of Fisheries, 2019)
Hilsa Tenualosa ilisha Â (Hamilton, 1822), one of the important commercial fish species in South Asian countries has received much attention for its conservation through captive breeding and seed production. The present study attempted to breed the fish by dry stripping in river Hooghly. Eggs were incubated at 22.8 and 28.30C temperatures in estuarine, pond and tap water. The hatching rate recorded was higher (p